2019
DOI: 10.11144/javeriana.uo38-80.caap
|View full text |Cite
|
Sign up to set email alerts
|

Condições associadas a atividade de planejamento nos centros de especialidades odontológicas

Abstract: Antecedentes: O planejamento nos serviços de saúde visa especificamente melhorar o estado de saúde de uma determinada população, garantindo o acesso com equidade e justiça, bem como agilizar a resposta do sistema de saúde às necessidades percebidas pela comunidade. Objetivo: Analisar a associação entre o relato da prática do planejamento nos Centros de Especialidades Odontológicas (CEO) com as características do município, do serviço e do gestor do serviço. Método: É um estudo de natureza quantitativa, onde se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 12 publications
(8 reference statements)
0
4
0
1
Order By: Relevance
“…Management. A study conducted by Lucena and colleagues in 2019 19 found that in BDSCs where managers exclusively performed this role and had additional training in public management or public health, there was a notable increase in the execution of planning activities, resulting in a higher and more e cient number of appointments.…”
Section: Discussionmentioning
confidence: 99%
“…Management. A study conducted by Lucena and colleagues in 2019 19 found that in BDSCs where managers exclusively performed this role and had additional training in public management or public health, there was a notable increase in the execution of planning activities, resulting in a higher and more e cient number of appointments.…”
Section: Discussionmentioning
confidence: 99%
“…Three management factors were associated with better quality scores: the existence of a manager in the DSC, the support for planning and organizing at the DSC, and the monitoring and analysis of goals. Previous evidence has shown that managers who work exclusively in the function, have more than two years in the position, and have complementary training in public management or public health tend to exercise greater planning in their activities 34 . Regarding the monitoring and analysis of the agreed goals, PMAQ‐CEO developed its evaluation policies based on payment for performance.…”
Section: Discussionmentioning
confidence: 99%
“…Previous evidence has shown that managers who work exclusively in the function, have more than two years in the position, and have complementary training in public management or public health tend to exercise greater planning in their activities. 34 Regarding the monitoring and analysis of the agreed goals, PMAQ-CEO developed its evaluation policies based on payment for performance. Studies have shown that when there are financial incentives, the number of dental procedures increases considerably, and the goals are met.…”
Section: Management Factorsmentioning
confidence: 99%
“…Além disso, as atividades de planejamento possivelmente ficam em segundo plano ao dever de cumprir suas metas clínicas. Nossos achados corroboram, mesmo que de forma inversa, aos resultados do estudo de Lucena et al (2019), que evidenciou que os CEO cujos gerentes atuam exclusivamente na função, possuem um tempo de atuação maior que 2 anos e que tem uma formação complementar na área de gestão pública ou de saúde coletiva tendem a realizar mais atividades de planejamento.…”
Section: Discussionunclassified